Pengaruh Metode Diskusi Pada Mata Kuliah Fisika Terhadap Pengetahuan, Sikap dan Pemahaman Belajar Mahasiswa Prodi Pendidikan IPA Universitas Tidar - Arini, Intan; Nurhayati, Syafira; Imawati, Riva (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
Abstract. This study aims to determine the learning outcomes of students who are taught physics using the discussion method on the knowledge, attitudes, and understanding of students about learning physics. This research was conducted at Tidar University to students of the Faculty of Teacher Training and Education (FKIP) Science Education study program. Based on research and data analysis that has been carried out on students of the Science Education study program, it is hoped that all students can carry out good learning activities and will increase students' understanding of knowledge, attitudes, and understanding in learning physics. This research was conducted online through Google form, using a quantitative approach with the type of Associative Research. The data collection technique was using the questionnaire method. The researcher used 45 respondents as a sample with the questionnaire distribution process carried out by giving questionnaires to respondents to students of the Tidar University Science Education Study Program who Have you ever taken a physics course Keywords: Methods of Discussion, Knowledge, Understanding,